2010
DOI: 10.1111/j.1399-0004.2010.01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital myasthenic syndrome associated with epidermolysis bullosa caused by homozygous mutations in PLEC1 and CHRNE

Abstract: Mutations in the plectin gene (PLEC1) cause epidermolysis bullosa simplex (EBS), which may associate with muscular dystrophy (EBS-MD) or pyloric atresia (EBS-PA). The association of EBS with congenital myasthenic syndrome (CMS) is also suspected to result from PLEC1 mutations. We report here a consanguineous patient with EBS and CMS for whom mutational analysis of PLEC1 revealed a homozygous 36 nucleotide insertion (1506_1507ins36) that results in a reduced expression of PLEC1 mRNA and plectin in the patient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 31 publications
(34 reference statements)
0
39
0
Order By: Relevance
“…]). Heteroallelic nonsense, frameshift, or splice-site mutations in PLEC were recently reported in 4 unrelated patients with documented defects in neuromuscular transmission [8284]. In two patients investigated by the author microelectrode studies of intercostal muscle EPs showed low-amplitude MEPPs.…”
Section: Postsynaptic Cmsmentioning
confidence: 99%
“…]). Heteroallelic nonsense, frameshift, or splice-site mutations in PLEC were recently reported in 4 unrelated patients with documented defects in neuromuscular transmission [8284]. In two patients investigated by the author microelectrode studies of intercostal muscle EPs showed low-amplitude MEPPs.…”
Section: Postsynaptic Cmsmentioning
confidence: 99%
“…Pathogenic mutations in plectin result in epidermolysis bullosa simplex, a progressive myopathy and, in some patients, a myasthenic syndrome [52]. Heteroallelic nonsense, frame-shift, or splice-site mutations in PLEC were recently reported in four unrelated patients [2, 53, 54]. In two patients microelectrode studies of intercostal muscle EPs showed low-amplitude MEPPs.…”
Section: Cms Caused By Plectin Deficiencymentioning
confidence: 99%
“…Morphologic studies revealed dislocated and degenerating muscle fiber organ-elles, plasma membrane defects allowing calcium ingress into the muscle fibers, and degeneration of the junctional folds, all attributable to lack of cytoskeletal support [2]. One patient harbored homozygous frameshift mutations in both PLEC and in CHRNE [54]. …”
Section: Cms Caused By Plectin Deficiencymentioning
confidence: 99%
“…The kinetic mutations fall into two categories according to whether they induce slow or fast channel syndromes [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Defects In Acetylcholine Receptor Subunitsmentioning
confidence: 99%
“…These are the pre-synaptic acetyltransferase CHAT 6 , the gene COLQ 7-8-9 encoding the triple stranded collagenic tail of the synaptic acetylcholinesterase (AChE), the genes encoding the different subunits of the postsynaptic acetylcholine receptors (AChR) CHRNA1, CHRNB1, CHRND, CHRNE and CHRNG, the RAPSN gene encoding the postsynaptic protein rapsyn 10 , the postsynaptic muscle specific kinase (MUSK) gene 11 , the postsynaptic sodium channel (SCN4) 12 , the DOK7 gene encoding the postsynaptic Dok-7 protein [13][14] , the LAMB2 encoding the synaptic Laminin B2 protein 15 , the AGRN gene encoding the postsynaptic agrin protein 16 and the PLEC1 gene encoding the postsynaptic protein plectin. 17-18-19 Genetic classification of the different CMS cohorts reveals that the majority of CMS patients have mutations in genes expressing postsynaptic endplate proteins [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] (table 1). Despite tremendous progress in identifying the molecular basis of the different CMS subtypes, almost half of the CMS population remains genetically undiagnosed.…”
Section: Introductionmentioning
confidence: 99%